2019
DOI: 10.3390/ma12142291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Metakaolin Using Nano-Silica on the Mechanical Properties and Durability of Concrete

Abstract: This paper discussed the effects of modified metakaolin (MK) with nano-silica (NS) on the mechanical properties and durability of concrete. In the first phase, trial mixes of concrete were prepared for achieving the desired value of the 28 days compressive strength, and the charge passed in rapid chloride permeability test (RCPT). In the second phase, statistical analysis was performed on the experimental results using the response surface method (RSM). The RSM was applied for optimizing the mix proportions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Textile reinforced concrete (TRC) has the superior characteristics of crack resistance, impact resistance, and durability properties, which has been widely applied in lightweight thin-walled structures, such as large span arches, shells, and domes [1][2][3]. TRC matrix has a better flowability because of the coarse aggregates completely replaced by the fine aggregates with different gradations, but the strength, stiffness, and elastic modulus of TRC matrix are adversely affected [4,5]. Therefore, developing a fine-grained matrix concrete with good strength and flowability is the first step is to achieve the excellent performance of TRC.…”
Section: Introductionmentioning
confidence: 99%
“…Textile reinforced concrete (TRC) has the superior characteristics of crack resistance, impact resistance, and durability properties, which has been widely applied in lightweight thin-walled structures, such as large span arches, shells, and domes [1][2][3]. TRC matrix has a better flowability because of the coarse aggregates completely replaced by the fine aggregates with different gradations, but the strength, stiffness, and elastic modulus of TRC matrix are adversely affected [4,5]. Therefore, developing a fine-grained matrix concrete with good strength and flowability is the first step is to achieve the excellent performance of TRC.…”
Section: Introductionmentioning
confidence: 99%
“…Silica fume has a high cost and is mainly used for concrete with high or ultra-high performances, with replacement dosages up to 10% in mass of binder. Metakaolin addition, despite having significant energy footprint and cost associated to its production, is eco-friendlier than Portland cement and it can also improve fresh and hardened properties when used in binary or ternary binder combination [26,27]. Nevertheless, fly ash addition is well known by its fineness and the spherical shape of its particles, which allows high water reductions and the increase of concrete packing density, resulting in significant performance improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant achievements had been made in the research on nanoparticle-modified cement, concrete, and other traditional building materials [16][17][18][19][20][21], and positive exploration had also been achieved in the modification of soil stabilizers. Shafiq [22] and Murthy et al [23] discussed the influence of nano-SiO 2 on the mechanical properties and durability of concrete. Kong et al [24] found that nano-SiO 2 could effectively improve the unconfined compressive strength of loess and improve pore structure.…”
Section: Introductionmentioning
confidence: 99%